2022
DOI: 10.1038/s41598-022-22233-w
|View full text |Cite
|
Sign up to set email alerts
|

An external validation study of the Score for Emergency Risk Prediction (SERP), an interpretable machine learning-based triage score for the emergency department

Abstract: Emergency departments (EDs) are experiencing complex demands. An ED triage tool, the Score for Emergency Risk Prediction (SERP), was previously developed using an interpretable machine learning framework. It achieved a good performance in the Singapore population. We aimed to externally validate the SERP in a Korean cohort for all ED patients and compare its performance with Korean triage acuity scale (KTAS). This retrospective cohort study included all adult ED patients of Samsung Medical Center from 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The predictive model used in this study incorporated various variable, including demographic, diagnosis code, administrative information and Charlson comorbidity Index. Similarly, an ED triage tool, the Score for Emergency Risk Prediction (SERP), to predict mortality within 2 to 30 days for ED patients was initially applied in a cohort from a Singaporean ED and subsequently underwent external validation in a South Korean ED 20,21 . These studies demonstrated AUCs of 0•81 − 0•82 for in-hospital mortality and 0•80 − 0•82 for 30-day mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive model used in this study incorporated various variable, including demographic, diagnosis code, administrative information and Charlson comorbidity Index. Similarly, an ED triage tool, the Score for Emergency Risk Prediction (SERP), to predict mortality within 2 to 30 days for ED patients was initially applied in a cohort from a Singaporean ED and subsequently underwent external validation in a South Korean ED 20,21 . These studies demonstrated AUCs of 0•81 − 0•82 for in-hospital mortality and 0•80 − 0•82 for 30-day mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…44 In particular, when considering that decisions made by the triage system can result in death (in case of a wrong decision) or the saved life, the legal and ethical implications require that the model be transparent, even to enable medical staff to have counterintuitive choices. We should report that only a few works by Yu et al 43 and Liu et al 28 pay attention to the explainability of their models. Consequently, the development of explainable AI models is a promising area.…”
Section: Prediction Of Triage Levelsmentioning
confidence: 95%
“…The problem of explainability of ML models has been explicitly faced by Leung et al 30 The authors of this paper proposed an interpretable ML model for predicting hospitalisation. Yu et al, 43 developed an interpretable ML model to calculate a Score for Emergency Risk Prediction for each patient. The score is validated as a predictor of mortality in the ED.…”
Section: Prediction Of Triage Levelsmentioning
confidence: 99%
“…Moreover, it enables users to build transparent and interpretable clinical scores quickly in a straightforward manner. It has been extensively used in different clinical applications, e.g., for general risk assessments in the emergency department, 22 , 23 , 35 , 36 and for prediction of disease-specific outcomes in specific patient cohorts. 24 , 25 , 26 , 37 , 38 , 39 , 40 , 41 …”
Section: Expected Outcomesmentioning
confidence: 99%